An implementation and evaluation of an RFC-based DCCP module for network simulator 2 - Perez, Joel Capisanan (2009)
This work aims to contribute to the effort of the research community to model and predict the behavior of DCCP in multi-protocol network environments.While an actual implementation is extremely useful, it is often not practical to model the behavior of applications using an actual implementation since it will cost more time and resources. The value of simulation in modeling, characterizing and predicting the behavior of new protocols and applications is well-known to research. The work in this thesis therefore plays a complementary role to the existing and future deployments of DCCP.This work implemented a module for NS-2 from an updated DCCP standard described in RFC 434. With this model of DCCP, the behavior and performance of the two currently defined Congestion Control Identifiers was evaluated, particularly CCID2 and CCID4 that were standardized by RFC 4341 and 4342 respectively.Lastly, through simulation studies that were designed to mimic multi-protocol scenarios and also via behavioral comparison of the DCCP module with a Linux kernel implementation, the behavior, throughout, and fairness of DCCP in comparison with TCP and UDP were studied more thoroughly.
Thesis (M.S. Electrical Engineering) -- University of the Philippines, Diliman.
Keywords: Computer network protocols -- Design; Datagram Congestion Control Protocol (DCCP).